Recent Developments in Methanol Technology by Air Liquide for CO2 Reduction and CO2 Usage. Issue 11 (9th September 2022) - Haag, Stéphane; Drosdzol, Christopher; Williams, Bryce; Peña, Vincent; Palauschek, Norbert; Wilken, Michael; Günther, Armin; Gronemann, Veronika; Roesch, Alexander
Abstract: Within the energy transition and decarbonization of the industrial sector, one of the main challenges is identifying competitive solutions to capture CO2 from chemical and energy plants to reduce emissions. The reduction of the carbon footprint as well as the valorization of CO2 ‐rich gases are of increasing interest for many industries and methanol is a perfect fit for energy storage, for producing clean fuels, and as building block for producing high value chemicals. In this article, an update of recent developments by Air Liquide Engineering & Construction regarding methanol technology is provided, focusing on CO2 reduction of large‐scale plants and on new solutions for CO2 utilization. For large‐scale methanol plants, drop‐in solutions using carbon capture technologies can be proposed to dramatically decrease the CO2 emissions. Abstract : In this work, Air Liquide presents the recent developments in methanol technology for CO2 reduction and CO2 usage with a clear strategy on how to reduce the carbon footprint of existing large‐scale methanol plants based on natural gas as feedstock and on how to improve CO2 ‐based methanol using green hydrogen for small‐scale units.